Não-cumulatividade do PIS e da COFINS: uma visão pragmática - Xavier, Raquel Mercedes Motta (2008)
The main of this paper was to analyze the non-cumulativeness of social contributions taxes PIS and COFINS, in a pragmatic perspective way. An interpretation for the noncumulativeness system based on these taxes context, and which available the effectiveness of this system was sugested. First, the paper defined cumulativenesses term, and presented the existing methods that can be used to avoid the occurrence of its effects. Then, PIS and COFINS non-cumulativeness normative structure was presented, opportunity that the constitutional norm and the norm which effects non-cumulativeness, also called credit right norm , were analyzed. Finally, the main statements that belong to the non-cumulativeness law system were interpreted based on the aim of non-cumulativeness and the social contributions context